EXPLORATION OF INDIGENOUS BACTERIA WITH POTENTIAL FOR TOTAL AMMONIA NITROGEN DEGRADATION FROM RUBBER WASTEWATER AND PHYLOGENETIC TREE CONSTRUCTION BASED ON 16S rRNA GENE SEQUENCES - Melinda, Annisa; Febria, Fuji Astuti; Tjong, Djong Hon (Jurnal Pendidikan Matematika dan IPA, 2025)
Rubber wastewater contains total ammonia nitrogen (TAN) at levels that can potentially cause pollution if discharged into water bodies without proper treatment. TAN content is one of the commonly used parameters for assessing water quality. Certain groups of bacteria are capable of naturally degrading TAN in the environment. This study aimed to isolate bacteria from rubber wastewater, evaluate their potential to degrade TAN, and identify the most effective isolate at the molecular level. Samples were collected from wastewater treatment ponds using random purposive sampling based on specific criteria. A survey method was used to determine sampling locations, while experimental methods were applied in the laboratory. Bacterial isolation was conducted using the serial dilution technique, followed by inoculation with the pour plate technique. Pure isolates were obtained using the streak plate technique. The degradation potential of the bacterial isolates was tested by inoculating 10% v/v of each isolate into 200 mL of rubber wastewater, followed by incubation at room temperature for six days. TAN levels were analyzed using the phenate method with a spectrophotometer, following the Indonesian National Standard SNI 06-6989.30-2005. Three bacterial isolates (NS-1, NS-2, and NB-1) were obtained from the rubber wastewater. All three isolates demonstrated potential in reducing TAN levels, with final TAN concentrations after incubation ranging from 6.75 to 4.8 mg/L, corresponding to a reduction of 52.50"“66.90%. The most effective isolate in reducing TAN was NS-2. Molecular identification using the PCR-seq method of the 16S rRNA gene revealed that isolate NS-2 showed 99.86"“99.93% sequence identity with Enterobacter sp. This study provides a basis for the development of bioremediation technologies for rubber wastewater treatment to improve aquatic environmental quality.